Elementary Geometry for College Students (5th Edition)

Published by Brooks Cole
ISBN 10: 1439047901
ISBN 13: 978-1-43904-790-3

Chapter 10 - Section 10.1 - The Rectangular Coordinate System - Exercises: 8d

Answer

$d = 2 \sqrt {(c - a)^{2} + (d - b)^{2}}$

Work Step by Step

$d = \sqrt {(2c - 2a)^{2} + (2d - 2b)^{2}}$ $d = \sqrt {(2(c - a))^{2} + (2(d - b))^{2}}$ $d = \sqrt {4(c - a)^{2} + 4(d - b)^{2}}$ $d = \sqrt {4((c - a)^{2} + (d - b)^{2})}$ $d = 2 \sqrt {(c - a)^{2} + (d - b)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.